The Influence of Learning Styles, Parental Income Levels, and Student Learning Motivation on Student Learning Achievement - Aji Wibowo, Wahyu (Journal of Social Knowledge Education (JSKE), 2023)
Purpose of the study: This study aims to determine: (1) the influence of learning styles on learning achievement; (2) the effect of parents' income level on learning achievement; ((3) the effect of Learning Motivation on Learning Achievement, (4) the influence of Learning Style, Parental Income Level, and Learning Motivation together on Learning Achievement. Methodology:This study was an ex post facto study. The population used in this study were students majoring in economics education with a total of 84 students. The instrument validity test used the product moment correlation formula and the reliability test used the internal consistency formula. The data prerequisite test was carried out by normality, linearity and multicollinearity test. The data analysis technique used is multiple regression analysis. Main Findings: Based on the results of this study it is known: (1) there is a positive and significant effect of Learning Style on Learning Achievement, with a tcount of 4.354 and a significance of 0.000; (2) there is a positive and significant effect of parents' income level on learning achievement with a tcount of 4.266 and a significance of 0.000; (3) there is a positive and significant effect of Learning Motivation on Learning Achievement with a tcount of 5.665 and a significance of 0.000; (4) there is a positive and significant effect of Learning Style, Parental Income level, and Learning Motivation together on Learning Achievement with Fcount of 115.623 and a significance of 5% and a coefficient of determination (R2y(1,2,3)) of 0.807. Novelty/Originality of this study:The novelty of this research is combining three main variables: learning style, parental income level, and student learning motivation, this research expands our understanding of the complex interactions between internal and external factors that influence academic achievement.